PENGEMBANGAN MEDIA REALIA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Ninik Kuswariyanti (Program Studi Pendidikan Matematika, 2021)
Realia media is a real object that can be used as a tool in learning activities. The purpose of this study was to improve student learning outcomes in mathematics with division material. The research method used was classroom action research in grade 2 SD Negeri Kedungcaluk 1, Krejengan District, Probolinggo Regency. The results showed that the test scores of student learning outcomes from pre-cycle to cycle 1 then cycle 2 increased significantly. In addition to improving learning outcomes, media relia also fosters enthusiasm and motivation for student learning as well as trains the independence of students to reason well in finding their own traditional distribution algorithms.